Pemberdayaan Masyarakat Desa Berbasis Angka Putus Sekolah (APS) untuk Pencapaian Target SDGs - Paramata, Dewi Diana; Umar, Masri Kudrat; Setiawan, Dewa Gede Eka (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2024)
Community empowerment is an effort to increase the power or strength of the community by providing encouragement, opportunities, opportunities, and protection by not regulating and controlling community activities that are empowered to develop their potential so that the community can increase their abilities and actualize themselves or participate through various activities. Community empowerment is basically a process of growth and development of community power to be involved in various aspects of development in an area. With the empowerment can release the community from backwardness. The purpose of this activity is to provide motivation for out-of-school children to be able to return to school through empowerment and mentoring activities based on motivational and non-academic classroom learning. This activity is expected to be useful for out-of-school children so that they can participate in activities well and receive learning materials through guidance by KKN students and can produce recommendations for forms of activities to the government in order to minimize the dropout rate. The expected result of this activity is the presence of data on children dropping out of school so that educational problems in the village are resolved. Increasing the capacity of village officials in the preparation and use of digitalized village data platforms to realize a digitized village. Pemberdayaan masyarakat adalah upaya untuk meningkatkan daya atau kekuatan pada masyarakat dengan cara memberi dorongan, peluang, kesempatan, dan perlindungan dengan tidak mengatur dan mengendalikan kegiatan masyarakat yang diberdayakan untuk mengembangkan potensinya sehingga masyarakat tersebut dapat meningkatkan kemampuan dan mengaktualisasikan diri atau berpartisipasi melalui berbagai aktivitas. Pemberdayaan masyarakat pada dasarnya adalah suatu proses pertumbuhan dan perkembangan kekuatan masyarakat untuk ikut terlibat dalam berbagai aspek pembangunan di suatu wilayah. Dengan adanya pemberdayaan bisa melepaskan masyarakat dari keterbelakangan. Tujuan dari kegiatan ini adalah pemberian motivasi bagi anak-anak putus sekolah untuk dapat kembali ke sekolah melalui kegiatan pemberdayaan dan pendampingan berbasis pembelajaran kelas motivasi dan non akademik. Kegiatan ini diharapkan bermanfaat untuk anak-anak putus sekolah sehingga mengikuti kegiatan dengan baik dan menerima materi pembelajaran melalui bimbingan oleh mahasiswa KKN dan dapat menghasilkan rekomendasi bentuk-bentuk kegiatan kepada pemerintah guna meminimalisir angka putus sekolah. Hasil yang diharapkan dari kegiatan ini adalah terdapatnya data anak putus sekolah sehingga permasalahan pendidikan di desa teratasi. Peningkatan kemampuan aparat desa dalam penyusunan dan penggunaan platform data desa secara digitalisasi untuk mewujudkan desa digitalisasi.